PENGARUH USER INTERFACE RESPONSIVE MOBILE WEBSITE TERHADAP JUMLAH VISITOR WEBSITE PANDANHOUSE.COM - Sinata, Frans (Jurnal Algoritma, Logika dan Komputasi, 2023)
The Human Centered Design (HCD) method is one of the methods in design and development that focuses on users according to their needs, habits and capabilities. The problem that is often faced is to access information on the pandanhouse website in terms of appearance that does not yet support the appearance of responsive web design on smartphone devices. The initial stages in this method start from the observation stage which aims to find out the problems faced by users in accessing the pandanhouse.com website to the testing stage to find out if the solutions provided can be understood and easily used by users. At the testing stage, the user is given tasks to interact directly with access to information on the Pandanhouse website through a smartphone device, as the final result of the test, it is expected that the user is sufficiently familiar and user friendly on the website on the responsive mobile website feature.